Effect Of Graded Substitution Levels Of Pigeon Pea (Cajanus Cajan) Leaf Meal For Berseem Leaf Meal On Broiler Performance - Esam Eldin Eltayeb; Salah Ahmed Abdulmuttalab; Rachmat Wiradimadja; Tuti Wijastuti; Ana Rohana tarmidi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
The main object of this study was to assess the productive and physiological responses of broiler chickens to dietary Pigeon Pea (Cajanus cajan) Leaf Meal (PPLM) as an ingredient. 200 day-old, unsexed Ross (303) broiler chicks were used as experimental birds; they were distributed to (5x10x4) following the completely randomized design (CRD). Experimental diets were formulated to (0.0%, 2.5%, 5.0%, 7.5% and 10.0% PPLM), at the expense of alfalfa meal which was included at 10.0% in the control diet. Feed and water were provided ad labium. Experimental period lasted for 7 weeks. Results revealed that there was a significant difference (P<0.05) in feed intake between level (2.5% - 5.0%), PPLM and control. There was no significant difference in total body weight gain. Feed conversion ratio (FCR) results showed that all birds fed PPLM were lagging after control, no significant difference detected between control and 5.0% PPLM. In conclusion the study showed that Pigeon pea (Cajanus cajan) leaf meal could be included in broiler diets at level 2.5-5.0% without any adverse effects on broiler performance.